(untitled) (Indo-American Journal of Life Sciences and Biotechnology, 2022)
Many error-tolerant applications rely on multiplication as a fundamental function. Approximate multiplication is regarded as an efficient method for balancing performance and accuracy against energy consumption. As a result, this research presents a low-power and compact multiplier for accurate, scalable approximate computation. A carry-maskable adder and an approximate tree compressor (ATC) make up the proposed approximate multiplier (CMA). By adopting a simple circuit topology and a simple carry-masking technique, ATC compresses partial products while the CMA provides precision scaling. This approximate multiplier reduces both power consumption and circuit area when compared to the Wallace tree multiplier, according to the experimental designs.